(untitled) (Nordic Journal of Practical Theology, 2024)
Liturgy and rituals do not seem to be the obvious tools for fighting against climate change. It might even make the situation worse by providing false hopes at a time when several tipping points already have passed. But, in the words of eco-theologian Larry Rasmussen, “religion addresses the big questions of life through elaborate symbol systems—rites and rituals, sacraments, and stories» dealing with death and renewal (Rasmussen, 2013, 34). I will thus argue that liturgy still have something to offer in the face of ecological crisis. Building on insights from performance studies, ritual studies and the works of thinkers such as Diana Taylor and Sara Pike, I apply an eco-liturgical approach for interpreting two diverse ritual expressions. The first is an altarpiece by Gunnar Torvund, “Tree of life” in Voksen Church, Oslo. The other is a “march of grief for extinct species” arranged by Extinction Rebellion in Oslo prior to the 2021 parliamentary elections in Norway. I conclude by arguing for eco-liturgical practice in the intersection of contemplation and activism.